Karakteristik Ekstrak Kulit Buah Kakao (Theobroma cacao L.) sebagai Sumber Antioksidan pada Perlakuan Ukuran Partikel dan Waktu Maserasi - Pratyaksa, I Putu Lingsan; Ganda Putra, G.P.; Suhendra, Lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2020)
Cocoa pod husk has not been used optimally by farmers, most of cocoa pod husk will discarded around the cacao tree or collected in one hole and then piled with soil. Cocoa pod husk waste can be used optimally by extracting polyphenol compounds which are used as natural antioxidant ingredients. This research aimed to determine the effect of particle size and maceration time on cocoa pod husk extract as a source of antioxidant and determine the best particle size and maceration time to produce cocoa pod husk extract as a source of antioxidants. This research used  factorial randomized block design with two factors. Factor 1 is a particle size consisting of 40, 60, and 80 mesh. Factor 2 is maceration time consisting of 24, 36, and 48 hours. The data were analyzed by analysis of variance and then it will be proceed with tukey test. The results showed that particle size and maceration time affected yield, total phenolic and antioxidant capacity of cocoa pod husk extract, while the interaction was affected on total phenolic and antioxidant capacity but had no effect on yield of cocoa pod husk extract. The best treatment to produce cocoa pod husk extract as a source of antioxidants 80 mesh particle size and maceration time for 48 hours, with a yield value of 5.22 ± 0.05 percent, a total phenolic of 148.09 ± 0.00 mg GAE / g and antioxidant capacity of 118.71 ± 0.13 mg GAEAC / g. Keywords: cocoa pod husk, extraction, antioxidants, particle size, maceration time